Sustainable Digital Transformation in Healthcare: Challenges and Directions in the Society 5.0 Era - Haryo Kusumo; Dian Marlina; Achmad Solechan (Advance Sustainable Science Engineering and Technology, 2025)
This study conducts a comprehensive literature review on the digital transformation required by health service institutions during the Society 5.0 era. Utilizing articles related to digital transformation and health services, the study presents qualitative data simplified into descriptive narratives to draw meaningful conclusions. The method employed is a qualitative literature review. The review identifies significant challenges, including big data utilization, data security, privacy concerns, and the implementation of cloud computing systems. Furthermore, the research synthesizes current trends and proposes actionable recommendations for overcoming these challenges, such as adopting Health 5.0 and fostering integrated Community 5.0 systems. The study underscores the importance of maintaining the human aspect amidst technological advancements. Future research directions are outlined, focusing on the "big data-based society" within Society 5.0 to explore innovative solutions, mitigate barriers, and ensure sustainable digital transformation in healthcare services.